Key international references for the redesign of a curriculum: competences for a Computer Science program - Garita-González, Gabriela (2021)
The objective of this research was to identify and contrast key international references in search of quality parameters to define the main components of a higher education computer program. This qualitative and exploratory research began in January 2019 with a team of 21 university academics and expert researchers. The focus group technique was used in the three workshops held with staff and authorities from the Information Systems program from Universidad Nacional in Costa Rica. One of the main results was the creation of a consensual list of formative professional competences for the Bachelor’s degree having Computer Sciences as the common trunk and Information Systems as the emphasis. It is concluded that the designed components include international technical criteria and that, in particular, the exit profile that was established takes into consideration technical competences, technical competences for the emphasis, and transversal competences.